In Vitro Assessment of Single-Retainer Tooth-Colored Adhesively Fixed Partial Dentures for Posterior Teeth - Tissiana Bortolotto; Carlo Monaco; Ioana Onisor; Ivo Krejci (International Journal of Dentistry)
The purpose of this paper was to investigate, by means of marginal adaptation and fracture strength, three different types of single retainer posterior fixed partial dentures (FPDs) for the replacement of a missing premolar. Two-unit cantilever FPDs were fabricated from composite resin, feldspathic porcelain, and fiber-reinforced composite resin. After luting procedures and margin polishing, all specimens were subjected to a Scanning Electron Microscopic marginal evaluation both prior to and after thermomechanical loading with a custom made chewing simulator comprising both thermal and mechanical loads. The results indicated that the highest score of marginal adaptation, that is, the closest score to 100% of continuous margins, at the tooth-composite resin interface was attained by the feldspathic porcelain group (88.1% median), followed by the fiber-reinforced composite resin group (78.9% median). The worse results were observed in the composite resin group (58.05% median). Fracture strength was higher in feldspathic porcelain (196N median) when compared to resin composite (114.9 N median). All the fixed prostheses made of fiber-reinforced composite resin detached from the abutment teeth before fracturing, suggesting that the adhesive surface's retainer should be increased.